2010
DOI: 10.1111/j.1463-1318.2010.02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiotherapy for rectal cancer: a comparison between intravenous 5‐fluorouracil and oral capecitabine

Abstract: Preoperative chemoradiotherapy with capecitabine for rectal cancer is efficacious and comparable to 5-FU (IV). It is more convenient, is well tolerated and avoids the need for inpatient admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…However, there were heterogeneities between these trials ( I = 53%, P = 0.05). Four trials [12, 15, 18, 19] reported N downstaging (the reduction of the N stage by at least one level after neoadjuvant chemoradiation); random-effect pooled estimate demonstrated an increased OR for capecitabine as well (OR, 2.06; 95% CI, 1.34–3.16; P = 0.001) (Figure 5). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there were heterogeneities between these trials ( I = 53%, P = 0.05). Four trials [12, 15, 18, 19] reported N downstaging (the reduction of the N stage by at least one level after neoadjuvant chemoradiation); random-effect pooled estimate demonstrated an increased OR for capecitabine as well (OR, 2.06; 95% CI, 1.34–3.16; P = 0.001) (Figure 5). …”
Section: Resultsmentioning
confidence: 99%
“…Four trials [12, 14, 16, 19] provided data for disease-free survival; however, Kaplan-Meier plots of disease-free survival were only available in 3 trials [12, 14, 19], including 690 patients (capecitabine, n = 330; 5-FU, n = 360). The meta-analysis of the pooled data demonstrated that the 3-year disease-free survival was in favour of capecitabine-based regimens (HR, 0.65; 95% CI, 0.44–0.96, P = 0.03; Figure 7).…”
Section: Resultsmentioning
confidence: 99%
“…Infusional 5-FU has been compared to Capecitabine in various trials. 13,14 The addition of oxaliplatin in neoadjuvant chemoradiation of rectal cancer has only added to the toxicity without any added benefit. 15 The published literature with respect to preoperative chemoradiation of rectal cancer is very scanty from India.…”
Section: Discussionmentioning
confidence: 99%
“…Patients often fail to follow up this therapy [9]. Xeloda is an oral fluoropyrimidine drug and has no cytotoxicity; while with TP, Xeloda turns into 5-Fu [10] in the tumor, which can cut into the tumor DNA strand and disturb its replication and repair and provide highly targeted tumor treatment.…”
Section: Discussionmentioning
confidence: 99%